Application Of Politeness Principles In The Study Of Aliyu Kamal’s Life Afresh - Mohammed Sheriff; Lawan Shu’aibu (The Journal of Studies in Language, Culture and Society)
northern Nigerian novelist, Aliyu Kamal. Behind series of utterances said or any expression uttered lies a motive or force that depicts the extent to which the participants involved in the talk exchange revere or defame one another. The reverence or otherwise may be about an object or a person being talked about that can either be in presence or absentia. Therefore, this paper attempts to explicate utterances among or between characters of this novel based on the application of politeness principles. These principles applied have different concepts like face saving acts, face threatening acts, deixis, and Leech’s politeness maxims (1983) that all form the target analysis of the novel. Qualitative approach with pragmatic content analysis has been the guiding tool in the identification of the utterances analysed from the novel. The dissection has revealed that the novelist employs some instances of expressions extractable from the novel to show levels of interaction that connect the characters in the novel. This can be extended to incorporate social contact existing in the novelist’s environment. It has also been found that language as an instrument can serve as a way to cultivate harmony, love, friendship, empathy, and even apathy and their like among interlocutors.